2019
DOI: 10.1088/1748-9326/ab574e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drought on dust storms: case study over Southwest Iran

Abstract: Dust storms are common meteorological events in arid and semi-arid regions, particularly in Southwest Iran (SWI). Here we study the relation between drought events in Iraq and dust storms in SWI between 2003 and 2018. The HYSPLIT model showed that central and southern Iraq are the main dust sources for SWI. Mean annual aerosol optical depth (AOD) analysis demonstrated that 2008 and 2009 were the dustiest years since 2003 and there is an increased frequency of summertime extreme dust events in the years 2008 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Javadian et al. (2019) also showed significant dust‐drought correlations over the Middle East. Achakulwisut (2018) and Javadian et al.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Javadian et al. (2019) also showed significant dust‐drought correlations over the Middle East. Achakulwisut (2018) and Javadian et al.…”
Section: Introductionmentioning
confidence: 91%
“…Achakulwisut (2018) showed that US Southwest and northern Mexico drought is highly correlated with the increases in Southwest dust. Javadian et al (2019) also showed significant dust-drought correlations over the Middle East. Achakulwisut (2018) and Javadian et al (2019) defined drought incorporating both precipitation and evapotranspirative demands.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Cao et al (215) indicated that the shrinkage of Horolazim wetland, especially in the southern and southwest parts of the wetland areas is the result of phenomena such as climate change, low-water periods, as well as negative effects of human activities that a conclusion supported by Javadian et al (2019) who found these wetlands to be one of the three most important dust centers affecting the other cities of Iran. Anthropogenic activities include extreme harvesting of water from wetland resources, wetland drying and converting into cropland, dams construction on the rivers, increasing human access to a wetland through construction roads inside wetland, an oil company drilling and undeniable impacts of Iran-Iraq war that have undesirable effect on the wetlands (Gerivani et al 2011).…”
Section: Main Local Dust Sources Due To Land Use/cover Changementioning
confidence: 97%
“…The cumulative effects of the threats have a high risk on this part of the wetland. Due to the construction of several dams and the implementation of irrigation network development projects in recent years, the drought has led to changes in the vegetation cover of these wetlands, which was identi ed as a source of dust (Javadian et al 2019). Rahimi Blouchi and Malekmohammadi (2013) showed that instead of the change in natural habitats, change in hydrological patterns due to dam construction and also water pollution has been identi ed as the most important risks of the Shadegan international wetland.…”
Section: Main Local Dust Sources Due To Land Use/cover Changementioning
confidence: 99%